Variation in the Non-mimetic Vocalizations of Brood-Parasitic Indigobirds and Their Potential Role in Speciation - DaCosta, Jeffrey M.; Sorenson, Michael D. (Frontiers in Ecology and Evolution, 2021)
Indigobirds (Vidua spp.) are obligate brood parasites in which imprinting on heterospecific hosts shapes adult vocal behavior and mating preferences. Adult male indigobirds mimic the songs and other vocalizations of their respective hosts, which signals their own host environment to prospective mates and has important implications for speciation. In this study, we examined variation within and among indigobird species in the non-mimetic components of their vocal behavior, including both chatter calls and their impressive repertoires of intricate non-mimicry songs. We test whether indigobird species in Tanzania differ consistently in general features of their non-mimetic vocalizations, differences that might contribute to reproductive isolation, and we test whether local ecological conditions influence vocal behavior. Indigobird non-mimetic song repertories are learned from and shared with other males of the same species. We find that local dialect “neighborhoods” are variable in size among species and regions, depending on habitat continuity and the distribution of male territories. Despite the complete turnover of the specific songs comprising the non-mimicry song repertoire from one local dialect to the next, we find significant species effects for more general measures of non-mimicry songs such as repertoire size and diversity, frequency, song length, and pace. For some traits, we also found significant regional differences, which may be mediated by significant relationships between elevation and morphometrics. Chatter calls were broadly similar across both species and localities, but we found significant species and region effects for frequency and to a lesser extent pace. We discuss the possibility that the effects of learning and mimicking the vocalizations of different hosts might explain many of the species differences we detected in non-mimetic vocalizations. Whether these differences are purely due to phenotypic plasticity or also reflect genetic divergence in sound production and/or female preferences, they may contribute to reproductive isolation among nascent and recently evolved indigobird species.